Partial Purification and Antibacterial Studies of Extracts from Eugenia jambolana Linn and Vinca rosea Linn (Biological Sciences - PJSIR, 2022)
EtOH five times, such that the last extract obtained, was almostcolourless. All EtOH extracts were concentrated under reducedpressure to a brownish gummy mass. This gummyextract was acidified with 10% HCl (Merck) and extractedwith CHC13 (Merck) to remove non-alkaloidal compounds.The acidic aqueous fraction was then basified with NH3 andextracted thoroughly with CHCI3.